Integrated Horticulture Development Project Report on Manipur and Tripura — Selected Districts(1994-2002) - Planning Commission (Planning Commission, 1994)
The North Eastern Region as a whole and Tripura and Manipur in particular are ideally suited for the development of horticulture crops. Mother nature has bestowed the most beautiful gifts to the North Eastern Region for raising several horticultural crops. the region has extremely beautiful landscape and immensely favorable agro-climatic conditions for raising a vaste range of horticultural wealth. In fact the region is the home of several important species.
Planning Commission Govt. of India